The Macroeconomic Impact of Bank Capital Requirements in Emerging Economies : Past Evidence to Assess the Future - Chiuri, Maria Concetta; Ferri, Giovanni; Majnoni, Giovanni (World Bank, Washington, DC, 2014)
The authors test for emerging economies, the hypothesis - previously verified only for the Group of 10 (G-10) countries - that enforcing bank capital asset requirements, exerts a negative effect on the supply of credit. Their econometric analysis of data on individual banks, suggests three main results: 1) Enforcement of capital asset requirements - according to the 1998 Basel standard - significantly curtailed credit supply, particularly at less-well-capitalized banks. 2) This negative effect is not limited to countries enforcing capital asset requirements in the aftermath of a currency, or financial crises. 3) The adverse impact of capital requirements on the credit supply was somewhat smaller for foreign-owned banks, suggesting that opening up to foreign investors, may be an effective way to partly shield the domestic banking sector from negative shocks. Overall, by inducing banks to reduce their lending, enforcement of capital asset requirements may well have induced an aggregate slowdown, or contraction in credit in the emerging economies examined. The results have relevance for the ongoing debate on the impact of the revision of bank capital asset requirements, contemplated by the 1999 Basel proposal. They suggest that in several emerging economies, the phasing in of higher capital requirements needs to be carefully managed, to avoid a credit supply retrenchment, which should not be underestimated.